Asymmetric modulation of solar activity on tropical cyclone frequency over the western North Pacific and the possible mechanism - Li, Delin; Xiao, Ziniu; Xu, Jianjun; Zhao, Liang (Frontiers in earth science (Lausanne), 2023)
The impacts of solar activity on the tropical Pacific climate have been widely reported. However, few studies focus on the effects of solar activity on the tropical cyclone (TC). Based on the observational and reanalysis data for 1979–2020, this study investigated the solar modulation of TC frequency over the western North Pacific in different solar cycle phases. Results suggest that the regressions of TC frequency to solar activity are asymmetric in the high- and low-solar activity years (HS and LS). Specifically, the intensified solar activity could markedly induce more TCs in HS; however, no significant modulation can be found in LS. Further exploration reveals a possible air–sea coupled mechanism for this interesting phenomenon. The relatively cloud-free area in the western North Pacific could receive more incoming solar radiation at the surface in HS than in LS. This increased regional surface net solar radiation in HS could produce a stronger surface upward latent heat flux and, thus, greater evaporation. Along with that, the local upward motion is dramatically enhanced over the TC source. Then, for compensation, the regional sea level pressure is reduced, and the low-level winds become cyclonic over the TC origin. All of these solar-caused regional atmospheric anomalies in HS contribute to more TC generations. The key to this possible mechanism is the increased regional solar forcing at the ocean surface that is amplified by regionally enhanced upward latent heat flux and evaporation.